核心蛋白聚糖decorin在非小细胞肺癌组织中低表达且与组织学类型相关 (Zhongguo Fei Ai Za Zhi, 2011)
BACKGROUND AND OBJECTIVE: Decorin is a protein component of the extracellular matrix. It has been proven that decorin plaid an important role in matrix assembly. The protein is also capable of suppressing tumor cell growth. The aim of this study is to examine the protein levels of decorin in tissue samples of non-small cell lung cancer (NSCLC) patients and evaluate its potential clinical value. METHODS: Decorin protein levels in tumor tissues and corresponding normal tissues from 16 cases of lung squamous cell carcinoma (SCC) were determined by Western blot analysis. Fifty-one NSCLC samples, including both tumor and normal lung tissues, were examined by immunohistochemical (IHC) staining. RESULTS: Western blot results showed that decorin protein levels in 75.0% (12/16) of the SCC tumor tissues were lower than those of the corresponding normal lung tissues. IHC results showed that positively stained decorin was detected in only 11.8% of the tumor tissues, significantly lower than that observed in normal alveoli tissues (53.1%, P < 0.001). In lung adenocarcinoma (ADC), almost no expression of decorin was observed, in contrast to squamous cell carcinoma (SCC) (P=0.006). CONCLUSION: Decreased levels of decorin in NSCLC tissue samples, particularly ADC cases, indicate that decorin could play a role in lung cancer carcinogenesis.